Types, Characteristics and Patterns In Tafsir of the Qur'an - Pandu Wijaya; Halimatussa’diyah; Hidayat, Rahmat (Tilawah: Journal of Al-Qur'an Studies, 2025)
This paper aims to examine more deeply to find out what types or sources or approaches to the interpretation of the Qur'an and what patterns or styles of interpretation exist in the tradition of interpretation of the Qur'an, this study uses library research, which means collecting data sources from books, commentaries, and journals that are relevant to the research subject, Interpretation of the Qur'an is a very complex field of science, with its characteristics focusing on the authenticity of sources, the correctness of methodology, and the relevance of context. From literal to symbolic, from scientific to legal, various types of interpretation show various perspectives. The pattern of interpretation shows the tendency of interpreters in studying the meaning of the Qur'an in various aspects, including legal, scientific, moral, spiritual, and social. Understanding thoroughly the characteristics, types, and patterns of interpretation is very important to avoid errors of interpretation and to maintain the depth of the meaning of the Qur'an according to the times.